Serum Fetuin-A Levels, QT Dispersion and P Dispersion in Dialysis Patients. (May 2013) - Taskapan, Mehmet Cagatay; Taskapan, Hulya; Comert, Melda; Temel, Ismail; Yagmur, Julide; Ulutas, Ozkan
<x xml:space="preserve">Abstract</x> Background: This study aims to find association of fetuin-A with serum lipids, QT dispersion (QT-d), and P dispersion (P-d) in dialysis patients. Methods: Fetuin-A serum levels were assessed in 50 dialysis patients. Results: Serum fetuin-A levels were significantly associated with QT-d (r = 0.289, p = 0.044), P-d (r = 0.39, p = 0.005), total cholesterol (r = 0.526, p = 0.000), low-density lipoprotein cholesterol (LDL-C) (r = 0.456, p = 0.00), triglyceride (r = 0.360, p = 0.011) and highly sensitive C-reactive protein (hsCRP) (r = −0.347, p = 0.030). In step-wise multiple regression analysis including being on hemodialysis (HD), presence of diabetes mellitus (DM), total cholesterol, LDL-C, triglycerides, hsCRP, only total cholesterol (b = 0.419, p = 0.03), and hsCRP (b = −0.316, p = 0.03) proved to be independent predictors of serum fetuin-A levels. QT-d showed a linear correlation with total cholesterol (r = 0.309, p = 0.029), LDL-C (r = 0.304, p = 0.038), P-d (r = 0.390, p = 0.005), and fetuin-A levels (r = 0.289, p = 0.044). In multiple regression analyses, the independent predictor of QT-d was being on HD (b = −0.417, p = 0.004), whereas total cholesterol, LDL-C, presence of DM, serum fetuin-A levels, and P-d had no independent effect on corrected QT (QT-C). Being on HD and age were important determinants of P-d whereas presence of DM, total cholesterol, LDL-C, fetuin-A, and QT-d had no independent effect on P-d. Conclusions: Lower fetuin-A levels are associated with high hsCRP and low cholesterol levels in dialysis patients.